Now I "See": The Impact of Graphic Novels on Reading Comprehension in High School English Classrooms. Issue 1 (2nd January 2017) - Cook, Mike P.
ABSTRACT: Few empirical studies have been conducted to investigate the educational uses of graphic novels. Because of this, misconceptions and stereotypes exist. This article presents findings from a study examining the effects of graphic novels on high school students' ( N = 217) reading comprehension. A graphic adaptation of a traditionally taught text (Poe's "The Cask of Amontillado") was explored as (a) a replacement text and (b) a supplemental text. The study design utilized a factorial analysis of variance with three independent variables: text type, grade level, and gender. A reading comprehension test was developed to serve as the dependent variable. Findings indicated significant effects for all factors. At the conclusion of the study, post interviews were conducted to elicit students' and teachers' perceptions of interacting with the graphic text.